(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
“Employee turnover” as a term is widely used in business circles. Although several studies have been conducted on this topic, most of the researchers focus on the causes of employee turnover but little has been done on the examining the sources of employee turnover, effects and advising variousstrategies which can be used bymanagers in various organisations to ensure that there is employeecontinuity in their organisations to enhance organizational competitiveness. This paper examines the sources of employee turnover, effects and forwards some strategies on how to minimizeemployeeturnover in organisations.